Addressing the Black-Box Challenge: Confidence Index Approach to Grading of Open-Ended Assessments in Accounting Education - Husain (Universitas Pendidikan Ganesha, 2025)
Traditional grading systems have long been a common practice in the world of cross-disciplinary education, but they face challenges such as limited scalability, inconsistencies in assessment, and a lack of personalized feedback. This condition encourages the emergence of an alternative in the form of an automatic assessment system based on artificial intelligence (AI). Although promising, this approach is not without problems, especially regarding the transparency and reliability of assessments which are often referred to as the